The Effect of Risk Management on Profitability: Empirical Study of Banking Companies Listed in Indonesian Stock Exchange 2019-2023 - Ainunnisa, Ditya Alfiena; Oktaviani, Delvi; Risman, Asep (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2024)
This study aims to examine the influence of Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), and Loan to Deposit Ratio (LDR) on Return on Assets (ROA). The research utilizes a sample of conventional banking companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2023. The sample selection method used is purposive sampling with a sample of 10 conventional banks. The results indicate that partially, Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) do not affect Return on Assets (ROA), while Non-Performing Loans (NPL) have a significant negative influence on Return on Assets (ROA). Risk management can serve as a mechanism to address profitability-related issues by maintaining the company's capital levels, and investors should pay closer attention to industry risks when investing in banking companies.